2016
DOI: 10.1007/s10753-016-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CysLTR1 and 2 in Maturating Lymphocytes of Hyperplasic Tonsils Compared to Peripheral Cells in Children

Abstract: Cysteinyl-leukotriene receptors 1 and 2 (CysLTR1 and 2) are related to allergic inflammatory responses. Recent studies demonstrated their role in lymphocyte division and maturation in the bone marrow. Few data are available about CysLTRs function in lymphocyte maturation in tonsils. The objectives of this study are to compare CysLTRs expression in peripheral blood lymphocytes with expression in maturating lymphocytes of hyperplasic tonsil and to check the influence of respiratory allergies in this process. Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…The chromosome 22q12.2 region includes POZ/BTB and AT hook containing zinc finger 1 (PATZ1), which is a transcription factor that interacts with p53 and may modulate p53-mediated apoptosis [37] . The region also contains phosphoinositide-3-kinase interacting protein 1 (PIK3IP1), which inhibits antitumor immunity [38] . The chromosome 13q14.2 region contains several genes of potential interest, including RB transcriptional corepressor 1 (RB1) and cysteinyl-leukotriene receptor 2 (CYSLTR2).…”
Section: Discussionmentioning
confidence: 99%
“…RB1 is a known tumor suppressor, which is frequently somatically deleted in CLL [ 32 ] . CYSLTR2 is part of the leukotriene pathway and thought to play a role in lymphocyte proliferation and maturation [ 39 ] .…”
Section: Discussionmentioning
confidence: 99%